Dimensional Distortion of Four Types of Intracanal Posts on CBCT Scans with Different Fields of View and Resolutions - Valizadeh, Solmaz; Karimi Nasab, Alireza; Iranparvar Alamdari, Mina; Vasegh, Zahra (Journal of Dental School, 2022)
Objectives This study assessed the dimensional distortion of four types of intracanal posts on cone-beam computed tomography (CBCT) scans with two different fields of view (FOV) in high and standard resolution modes. Methods This in vitro study evaluated 40 extracted single-rooted maxillary central incisors that underwent root canal treatment. The teeth were randomly assigned to 4 groups (n=10) for placement of non-tapered brass, silver, titanium and stainless steel (SS) intracanal posts. The diameter of the posts was measured at two reference points by a digital caliper (gold standard). The teeth underwent CBCT with 8 x 8 and 8 x 12 cm FOV with high and standard resolution modes. The post diameters were measured on axial CBCT images at the same reference points and compared with the gold standard. Data were analyzed by ANOVA, and paired and independent sample t-test. Results Significant differences were noted between the radiographic diameter of the posts and their actual size (P<0.05). Titanium posts (40.25%) showed minimum percentage of dimensional distortion followed by brass (54%), silver (62.5%) and SS (70.17%) posts. High-resolution images with 8 x 8 cm FOV yielded minimum dimensional distortion (40.6%) followed by high-resolution images with 8 x 12 cm FOV (45.75%), standard-resolution images with 8 x 8 cm FOV (68.75%), and standard-resolution images with 8 x 12 cm FOV (72.1%). Conclusion All metal posts showed significant dimensional distortion on CBCT scans, irrespective of the FOV size and resolution mode. SS posts yielded maximum, and titanium posts showed minimum dimensional distortion.